Sosialisasi Dampak Kekerasan Dalam Rumah Tangga terhadap Kesehatan Mental Korban Kekerasan Dalam Rumah Tangga di Negeri latuhalat - Ronald D. Hukubun; Rahman Rahman; Yemima H. Von Bulow; Kereison D. Saija; Regina Latuheru; Krisnawati Maahury (Universitas Maritim AMNI Semarang, 2023)
Acts of domestic violence can happen to anyone, but only a small portion emerges to the surface, while some are still submerged or unrecognized. This condition is influenced by the community's opinion that domestic violence is an internal family problem and should not be exposed, some people still cover up this condition because they maintain social status for them. Family unity and harmony can be disrupted if quality and self-control cannot be controlled, which can eventually lead to domestic violence resulting in a sense of insecurity, discomfort and injustice in the household. Cases of domestic violence show a trend that continues to increase from year to year. The purpose of implementing the activity is to increase awareness of the importance of the mental health of victims of domestic violence in Latuhalat Country. Besides that, the goal of this socialization is that the public knows the forms of domestic violence, the cycle of domestic violence, the impacts of domestic violence and how to overcome them.